2002
DOI: 10.1002/1521-379x(200202)54:2<51::aid-star51>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

New Sweet Potato Line having low Gelatinization Temperature and altered Starch Structure

Abstract: A new sweet potato breeding line, Kanto 116, was developed, featuring low gelatinization temperature and an altered starch fine structure. Starch granules from Kanto 116 showed an abnormal morphology characterized by cracking into granules. Starch content, amylose content and tuberous root appearance of Kanto 116 were similar to those of the control and the parents. Pasting temperatures of Kanto 116 starch determined by the Rapid Visco Analyser were 51.4 — 52.6 °C, approximately 20 °C lower than those of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…This result also agreed with previous reports that the short chains (, DP11) inhibited retrogradation of starch [26][27][28]. Furthermore, cracking of QS starch granules was observed around their granule center, which may be caused by changes in the crystallinity of the granules [2]. These distinctive features would be the reason for the high susceptibility of QS starch granules to the action of pancreatin.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result also agreed with previous reports that the short chains (, DP11) inhibited retrogradation of starch [26][27][28]. Furthermore, cracking of QS starch granules was observed around their granule center, which may be caused by changes in the crystallinity of the granules [2]. These distinctive features would be the reason for the high susceptibility of QS starch granules to the action of pancreatin.…”
Section: Discussionsupporting
confidence: 92%
“…The apparent amylose contents of the sweetpotato starches ranged from 13.6% to 16.2% and were similar to starches from 16 kinds of sweetpotato cultivars [3]. The amylose content of QS starch was slightly lower than that obtained in the previous report (QS is named as Kanto 116 in that report) [2], which may be due to differences in culture conditions and analytical standards of amylose and amylopectin. It was found that the content of attached phosphate groups decreased in the order of decreasing gelatinization temperature.…”
Section: Digestibility Of Starch Granules By Pancreatinmentioning
confidence: 50%
See 2 more Smart Citations
“…A aparência dos grânulos do amido de batata-doce (Figura 1) foi típica desta fonte de amido, com formatos redondos, ovalados e poligonais, os mesmos relatados por Cereda et al, 2001, Katayama et al, 2002, Hoover, 2001e Matsuguma, 2006 As superfícies dos grânulos apresentaram-se lisas e sem evidências de quebras, rachaduras após os tratamentos por TTBU. Alguns trabalhos da literatura também não observaram alterações em amidos de milho normal, ceroso e de alto teor de amilose tratados por TTBU (100 °C/16 horas) com 30% de umidade (HooVeR;MANUel, 1996).…”
Section: Microscopia Eletrônica De Varreduraunclassified